2004
DOI: 10.1002/ab.20055
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bullying and victimization among early adolescents: Associations with disruptive behavior disorders

Abstract: Bullying is a common problem faced by children and adolescents in schools. One hypothesis that needs to be examined regarding the causation of this problem is whether being a bully or a victim may stem from disparate underlying patterns of psychopathology. Results are particularly scarce regarding the association between bully-victim problems and disruptive behavior disorders. The present study sought to investigate the association between DSM-IV symptoms of Oppositional Defiant Disorder (ODD), Conduct Disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
3
23

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 36 publications
(42 reference statements)
10
61
3
23
Order By: Relevance
“…These results are consistent with those of Espelage andHolt (2001), Pateraki andHoundoumadi (2001), Seals and Young (2003), Scheithauer et al (2006), andNarayanan andBetts (2014); who found that bullying and victimization rates among males are higher than rates among females. However, the results are not in line with those of Peskin et al (2006), Kokkinos and Panayiotou (2004), and Kljakovic et al (2015), who found that males and females did not differ significantly on bullying or victimization.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These results are consistent with those of Espelage andHolt (2001), Pateraki andHoundoumadi (2001), Seals and Young (2003), Scheithauer et al (2006), andNarayanan andBetts (2014); who found that bullying and victimization rates among males are higher than rates among females. However, the results are not in line with those of Peskin et al (2006), Kokkinos and Panayiotou (2004), and Kljakovic et al (2015), who found that males and females did not differ significantly on bullying or victimization.…”
Section: Discussioncontrasting
confidence: 58%
“…Likewise, Kokkinos and Panayiotou (2004) conducted a study on a sample of adolescents aged 12-15, attending high schools in Cypris. They found no significant gender differences on bullying or on victimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Έρευνες που μελετούν τον ΠΕ και τη ΠΘ έχουν αναδείξει θετική συσχέτιση μεταξύ των δύο φαινομένων σε προέφηβους (Athanasiades, Kamariotis, Psalti, Baldry, & Sorrentino, 2015 · Kokkinos, 2013 · Kokkinos & Kipritsi, 2012· Kokkinos & Panayiotou, 2007 και έφηβους μαθη-τές (Kokkinos & Panayiotou, 2004), υποδεικνύοντας πως μια σημαντική μερίδα του υπό με-λέτη πληθυσμού έχει παρόμοιες πιθανότητες να εμπλακεί και στα δύο φαινόμενα (Kokkinos & Panayiotou, 2007). Ανάλογες συσχετίσεις εμφανίζονται μεταξύ του ΚΕ και της ΚΘ στα ίδια ηλικιακά φάσματα (Αντωνιάδου & Κόκκινος, 2013· Athanasiades, Baldry, Kamariotis, Kostouli, & Psalti, 2016· Athanasiades et al, 2015, οδηγώντας στο συμπέρασμα πως όχι μόνο ο ΚΕ μπορεί να προβλέψει την εμφάνιση της ΚΘ αλλά και το αντίθετο (Αντωνιάδου & Κόκ-κινος, 2013 · Antoniadou, · Athanasiades et al, 2016.…”
Section: σχέση μεταξύ διάφορων μορφών εκφοβισμού-θυματοποίησηςunclassified
“…Τέλος, θα πρέπει να επισημανθεί πως ορισμένες έρευνες δεν εντοπίζουν στατιστικά σημαντικές διαφυλικές διαφορές στον ΣΕ (Andreou, 2000 · Kokkinos & Panayiotou, 2004, 2007, στον ΚΕ (Αντωνιάδου & Κόκκινος, 2013· Athanasiades et al, 2015· Makri-Botsari & Karagianni, 2014, στην επιθετικότητα σχέσεων (Kokkinos, Voulgaridou, Mandrali, et al, 2016) Kokkinos, Antoniadou, & Markos, 2016) σε προέφηβους και έφηβους μαθητές. Σύμφωνα με τους Athanasiades et al (2015), χαρακτηριστικά που συνδέονται με το αρσενικό φύλο (π.χ.…”
Section: φύλοunclassified
“…En una fase inicial, la mayor parte de los estudios se centraron en la búsqueda de una definición del problema (Olweus, 1993;Rivers y Smith, 1994;Crick, Casas y Ku, 1999), para paralelamente, dejar paso a otros que focalizaron su atención en la incidencia del problema (Boulton, 1993;Olweus, 1996;Smith, Morita, Junger-Tas, Olweus, Catalano y Slee, 1999; Defensor del Pueblo, AA.VV., 1999), aspecto que aún hoy sigue preocupando y así lo reflejan la publicación de estudios específicos en los últimos cinco años (Carney y Merrel, 2001;Solberg y Olweus, 2003;Toldos, 2005;Avilés y Monjas, 2005;Cerezo y Ato, 2005;Ramírez, 2006). La descripción detallada del fenómeno favorece entonces, la aparición de estudios preocupados por la descripción de los agentes implicados (Rigby, 1997;Monks, Smith y Swettenham, 2003;Veenstra, Lindenberg, Oldehinkel, De Winter, Verhulst y Ormel, 2005;Camodeca y Goossens, 2005; Perren y Alsaker, 2006), el análisis de los factores causales del fenómeno (Lahey, Waldman y McBurnett, 1999;Kokkinos y Panayiotou, 2004;Farrington, 2005), y de estudios centrados en el análisis de los efectos que, en especial, el problema tiene entre las víctimas (Crick y Grotpeter, 1995;Perren y Alsaker, 2006). Como resultado final de toda la investigación previa y de los resultados obtenidos en estudios actuales, se está produciendo un aumento de investigaciones centradas en el diseño, desarrollo y evaluación sistemática de programas de intervención (Cowie y Olaffson, 2000;Trianes y García, 2002;Elinoff, Chafouleas y Sassu, 2004;Nordhagen, Nielsen, Stigum y Köhler, 2005; Benítez, Almeida y Justicia, en prensa).…”
Section: Introductionunclassified